2013
DOI: 10.1002/0471140856.tx1610s55
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Rodent Testis Co‐Cultures

Abstract: Male reproductive development is a complex process that is sensitive to disruption by a range of toxicants. There is a great need for in vitro models that can evaluate potential male reproductive toxicants. The current unit presents a protocol for preparation of a three-dimensional in vitro model of male reproductive development that reduces the number of animals required for evaluation of toxicants. A Matrigel overlay provides a three-dimensional extracellular matrix that improves cell attachment, viability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The goal of this model is to provide an in vitro alternative to in vivo models of male reproductive toxicity by using a 3D (‘organotypic’) culture that resembles the testis in structure and function. This co-culture includes the major testes cell types, including germ, Sertoli and Leydig cells (Yu et al 2005, Wegner et al 2013). We have also demonstrated that the addition of a Matrigel ™ overlay at an optimized concentration not only gave the testicular cells a three dimensional structure on which to grow, but also improved germ cell survival, enhanced cell survival pathways and reduced cell stress pathways (Yu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this model is to provide an in vitro alternative to in vivo models of male reproductive toxicity by using a 3D (‘organotypic’) culture that resembles the testis in structure and function. This co-culture includes the major testes cell types, including germ, Sertoli and Leydig cells (Yu et al 2005, Wegner et al 2013). We have also demonstrated that the addition of a Matrigel ™ overlay at an optimized concentration not only gave the testicular cells a three dimensional structure on which to grow, but also improved germ cell survival, enhanced cell survival pathways and reduced cell stress pathways (Yu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is thus an urgent need to develop effective and practical tools for early screening of chemicals with potential adverse effects using highthroughput, low-cost methodologies that ensure high predictability of human biological responses (Parks Saldutti et al, 2013). Recently, in vitro testicular models have been introduced to environmental chemical safety assessment to improve the predictability of chemical-induced testicular toxicity in human and elucidate mechanisms of chemical toxicity (Harris et al, 2015;Hofmann et al, 2005a;Parks Saldutti, et al, 2013;Wegner et al, 2013Wegner et al, , 2014Yu et al, 2003Yu et al, , 2005Yu et al, , 2009). Some of these in vitro models form a testicular-like multilayered architecture that mimics in vivo characteristics of seminiferous tubules (Yu et al, 2003(Yu et al, , 2005.…”
mentioning
confidence: 99%
“…However, these in vitro primary testicular cell coculture models still have the disadvantage of employing animals for the isolation of testicular cells. In addition, complicated isolation procedures lead to inconsistency of primary testicular cells (Wegner et al, 2013). In this study, we used a spermatogonial cell line (C18-4) to examine and compare the toxicity profiles of BPA and some of its analogues.…”
mentioning
confidence: 99%
“…This system is relatively inexpensive and sensitive and has been used to determine the toxic effects of a variety of compounds (34, 35). It must be noted, however, that this approach to screening compounds in vitro has a limitation in that the behavior of Sertoli cells in vitro may different from their behavior in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Melphalan and FSHβ-melphalan conjugates were evaluated for cytotoxicity using a lactate dehydrogenase release assay in a three-dimensional in vitro testicular co-culture model (34). In brief, the testes of male Sprague–Dawley rat pups (Harlan, Hayward, CA) were dissected from 5-day-old pups, decapsulated under a dissection microscope and the seminiferous cords/tubules were pooled and digested in a solution of 0.1% collagenase (Worthington Biochemical Corporation, Lakewood, NJ), 0.1% hyaluronidase (Sigma, St. Louis, MO), DNAse I (0.001 mg/ml, Sigma, St. Louis, MO), and Eagle’s minimal essential medium (MEM Life Technologies Inc., Gaithersburg, MD) for 20 min at 37°C (35, 36).…”
Section: Methodsmentioning
confidence: 99%